1993
DOI: 10.1055/s-0038-1651592
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Activity of SR 46349, a Novel, Potent and Selective 5-HT2 Receptor Antagonist

Abstract: SummarySR 46349 (trans-4-[(3Z)3-(2-dimethylaminoethyl)oxyimino-3(2-fluorophenyl)propen-1-yl] phenol, hemifumarate) is the first member of a newly-developed 5-HT2 antagonist series. SR 46349 potently inhibited serotonin-induced aggregation of rabbit and human platelets (IC50 = 1 and 3.9 nM respectively) but had no effect on the action of other platelet aggregating agents. SR 46349 was 118 and 25 times more potent than ketanserin against 5-HT + epinephrine-induced aggregation of rabbit and human platelets respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
11
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
4
11
1
Order By: Relevance
“…Whereas APD791 had no effect on ADP-induced aggregation per se, it was a potent inhibitor of 5-HT-mediated amplification. Similar results have been reported for other less selective 5-HT 2A antagonists including ketanserin, sarpogrelate (M-1), R-96544, SR 46349, and AR246686 (Van Nueten et al, 1981;Herbert et al, 1993;Ogawa et al, 2002;Adams et al, 2008). The IC 50 of APD791 inhibition of human platelet aggregation (8.7 nM) was consistent with its K i for the human 5-HT 2A receptor (4.9 nM).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Whereas APD791 had no effect on ADP-induced aggregation per se, it was a potent inhibitor of 5-HT-mediated amplification. Similar results have been reported for other less selective 5-HT 2A antagonists including ketanserin, sarpogrelate (M-1), R-96544, SR 46349, and AR246686 (Van Nueten et al, 1981;Herbert et al, 1993;Ogawa et al, 2002;Adams et al, 2008). The IC 50 of APD791 inhibition of human platelet aggregation (8.7 nM) was consistent with its K i for the human 5-HT 2A receptor (4.9 nM).…”
Section: Discussionsupporting
confidence: 84%
“…In conclusion, the present study demonstrates that APD791 is a potent, selective, and orally available 5-HT 2A receptor antagonist, and suggests that clinical evaluation of this drug is warranted because this profile offers potential improvements over previously described 5-HT 2A receptor antagonists (Van Nueten et al, 1981;Herbert et al, 1993;Ogawa et al, 2002). The combined inhibition of 5-HT-mediated thrombosis, vasoconstriction, and smooth muscle cell proliferation by APD791 could provide unique benefits for the treatment of thrombotic disease.…”
Section: Discussionmentioning
confidence: 61%
“…This is in contrast to the recent study and the previous studies performed in dogs, which reported, in the absence of exogenous 5-HT, inhibition by 5-HT 2A receptor antagonists on platelets in vivo and in vitro [3,16,17]. Platelet inhibition in the absence of exogenous 5-HT has also been observed in other species [11,12,14,15].…”
contrasting
confidence: 99%
“…A short survey of the literature shows that 5-HT 2A receptor antagonists have unequivocally been shown to inhibit 5-HT-potentiated platelet aggregation of PRP in humans and many other species in vitro and ex vivo [3,6,8,11,12] and 5-HT-stimulated thrombus formation in mice in vivo [13]. There are also animal studies reporting inhibition of aggregation induced by physiologic platelet stimuli (collagen, thrombin, ADP, and epinephrine) by 5-HT 2A receptor antagonists in vitro and ex vivo, and in thrombosis models in vivo, particularly in the Folts model of coronary occlusion in the dog [3,11,12,[14][15][16][17]. However, the results in humans are conflicting [5,[18][19][20].…”
mentioning
confidence: 99%
“…However, inhibitors of these receptors have been generally disappointing in the context of arteri al thrombosis, although antagonists to serotonin receptors have proved effective in experimental animal models of thrombosis [21]. Although the search is on for the optimal inhibitor of arterial thrombosis, it should not be forgotten that combinations of inhibitors may be more efficient than the individual compounds alone.…”
mentioning
confidence: 99%